PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. SARANA INTI INDOTAMA - Wulandari, Suci; Ananta Vidada , Irwin (PT. Intelek Cendikiawan Nusantara, 2025)
This research is motivated by the phenomenon of employee performance fluctuations at PT. Sarana Inti Indotama, suspected to be influenced by work environment and work motivation. The purpose is to determine the extent to which these factors affect employee performance. This quantitative research uses a survey approach. The population consists of 55 manufacturing employees, with a saturated sampling technique. Data were analyzed using SPSS 23.0 with several tests: data quality test, classical assumption test, multiple linear regression analysis, hypothesis testing, and coefficient of determination (R²) test. The results show that the work environment has a positive and significant effect on employee performance, with a t-value of 2.133 > t-table 2.006 and a significance of 0.038. Work motivation also shows a positive and significant effect, with a t-value of 3.180 > t-table 2.006 and a significance of 0.002. Simultaneously, both variables positively and significantly influence performance, with an F-value of 34.434 > F-table 3.17 and a significance of 0.000. The Adjusted R-Square value is 57%, while the remaining 43% is influenced by other variables outside this study Keywords: Work Environment, Work Motivation, and Employee Performance